Characteristics of patients with anaphylaxis to European hornet (Vespa crabro) venom compared to anaphylaxis to wasp (Vespula spp.) venom in southern Germany - Bertlich, Mattis Ralf Otfried; Weber, Felix; Bertlich, Ines; Kendziora, Benjamin; Ruëff, Franziska; Spiegel, Jennifer L.; French, Lars E.; Oppel, Eva (International archives of allergy and immunology, 2024)
Introduction: Systemic hypersensitivity to hymenoptera species venom is the most common cause for anaphylaxis in adults. Due to similarities between hornet (Vespa crabro) and wasp (Vespula spp.) venom, patients with hornet venom anaphylaxis are often treated similarly to wasp-allergic patients. However, comparative data are scarce. This study aimed to analyze differences and similarities between these two groups. Methods: A retrospective analysis with 42 patients with certain anaphylaxis to hornet venom was conducted. These were matched for age, gender, and CAP class with 42 patients with wasp venom anaphylaxis. Clinical outcomes and treatment adherence were compared. Results: Patients with hornet venom anaphylaxis showed a significantly higher degree of anaphylaxis (21 vs. 9 patients with grade III/IV anaphylaxis, p < 0.001), despite similar tryptase levels (6.3 ± 8.3 vs. 5.1 ± 4.2) or presence of mastocytosis (2 vs. 3). These patients also showed significantly lower therapy adherence, resulting in fewer patients undergoing specific immune therapy (29 vs. 37, p = 0.030) or sting challenges (14 vs. 27, p = 0.046). Both groups showed high efficacy of specific immunotherapy with wasp venom extract. Conclusion: Hornet stings induce more severe anaphylaxis, while patients with hornet venom allergies demonstrate lower treatment compliance, likely due to inadequate education. Specific immunotherapy with wasp venom extract remains effective for both.
Gesehen am 18.08.2025